Modulators of neuroinflammation have a beneficial effect in a Lafora disease mouse model - Mollá, Belén (Mol Neurobiol, 2021)
Lafora disease (LD; OMIM#274780) is a fatal rare neurodegenerative disorder characterized by generalized epileptic seizures and the presence of polyglucosan inclusions (PGs), called Lafora bodies (LBs), typically in the brain. LD is caused by mutations in two genes EPM2A or EPM2B, which encode respectively laforin, a glucan phosphatase, and malin, an E3-ubiquitin ligase. Much remains unknown about the molecular bases of LD and, unfortunately, appropriate treatment is still missing, therefore patients die within 10 years from the onset of the disease. Recently, we have identified neuroinflammation as one of the initial determinants in LD. In this work, we have investigated anti-inflammatory treatments as potential therapies in LD. With this aim, we have performed a preclinical study in an Epm2b−/− mouse model with propranolol, a β‐adrenergic antagonist, and epigallocatechin gallate (EGCG), an antioxidant from green tea extract, both of which displaying additional anti-inflammatory properties. In vivo motor and cognitive behavioral tests and ex vivo histopathological brain analyses were used as parameters to assess the therapeutic potential of propranolol and EGCG. After 2 months of treatment, we observed an improvement not only in attention defects but also in neuronal disorganization, astrogliosis, and microgliosis present in the hippocampus of Epm2b−/− mice. In general, propranolol intervention was more effective than EGCG in preventing the appearance of astrocyte and microglia reactivity. In summary, our results confirm the potential therapeutic effectiveness of the modulators of inflammation as novel treatments in Lafora disease.